Pengaruh ROA dan ROE terhadap EPS pada Perusahaan Indeks LQ45 yang terdaftar di Bursa Efek Indonesia Periode 2016-2019 - Khurrotul A'yun; Yeni Eva Damayanti (Fakultas Ekonomi dan Bisnis, Universitas Islam Raden Rahmat Malang, 2022)
This study aims to determine whether: 1) the effect of Return On Assets (ROA) partially on Earning Per Share (EPS), 2) the effect of Return On Equity (ROE) partially on Earning Per Share (EPS), 3) the effect of Return On Assets (ROA) and Return On Equity (ROE) simultaneously on Earning Per Share on LQ45 Index Companies listed on the Indonesia Stock Exchange (IDX) for the 2016-2019 period. To achieve this goal, this study uses quantitative methods using multiple linear regression analysis to view the data with the help of SPSS version 16.0 program. The sampling method used in this study was purposive sampling method and obtained as many as 40 samples from 45 populations in this study. The type of data used in this study is secondary data in the form of annual reports and company financial statements. The results of this study indicate that Return On Assets (ROA) partially has a significant negative effect on Earning Per Share (EPS), Return On Equity (ROE) has a significant positive effect on Earning Per Share (EPS). Simultaneously, the ROA and ROE variables have a significant effect on EPS